Synopsis of Lestes from Brazil with description of Lestes demarcoi sp. nov. (Zygoptera: Lestidae) - Lencioni, F.a.a.; Neiss, U.g.; Dutra, S.l.; Furieri, K.s.; Juen, L.; Batista, J.d.; Vilela, Diogo S. (Zootaxa, 2021)
The Brazilian fauna of Lestidae contains two genera (Archilestes Selys, 1862 and Lestes Leach in Brewster, 1815) with 14 species, many of which are poorly defined and/or known only by primary literature. To improve the knowledge of the Brazilian species of the genus Lestes we examined 97 specimens pertaining to 11 of the 13 described species. Additionally, a new species is described here in honor to Prof. Dr. Paulo De Marco Júnior: Lestes demarcoi (Holotype and Allotype: Brazil: Amazonas, Manaus, Reserva Adolpho Ducke, Acará trail, 02º55’46” S & 59º58’22” W, 62 m, 13.iv.2009, collected in tandem, U.G. Neiss leg. and deposited in FAAL). Diagnostic illustrations of all species are provided. Color photographs of live individuals of Lestes dichrostigma Calvert, 1909, Lestes forficula Rambur, 1842 and Lestes paulistus Calvert, 1909 are also presented.